A multi‐pathway perspective on protein aggregation: Implications for control of the rate and extent of amyloid formation. Issue 6 (31st January 2015) - Hall, Damien; Kardos, József; Edskes, Herman; Carver, John A.; Goto, Yuji
Abstract : The nucleation‐growth model has been used extensively for characterizing in vitro amyloid fibril formation kinetics and for simulating the relationship between amyloid and disease. In the majority of studies amyloid has been considered as the dominant, or sole, aggregation end product, with the presence of other competing non‐amyloid aggregation processes, for example amorphous aggregate formation, being largely ignored. Here, we examine possible regulatory effects that off‐pathway processes might exert on the rate and extent of amyloid formation – in particular their potential for providing false positives and negatives in the evaluation of anti‐amyloidogenic agents. Furthermore, we investigate how such competing reactions might influence the standard interpretation of amyloid aggregation as a two‐state system. We conclude by discussing our findings in terms of the general concepts of supersaturation and system metastability – providing some mechanistic insight as to how these empirical phenomena may manifest themselves in the amyloid arena. Abstract : Effects of amorphous aggregation on amyloid formation. Formalizes high‐dimensional aggregate isomer space. Rationalization of supersaturation and amyloid formation.